2007
DOI: 10.1002/hed.20614
|View full text |Cite
|
Sign up to set email alerts
|

Salivary duct carcinoma: A clinical and histologic review with implications for trastuzumab therapy

Abstract: Trastuzumab is effective in treating HER-2-positive breast cancer. Given immunohistochemical similarities between SDC and ductal carcinoma of the breast, patients with FISH-positive HER-2/neu SDC should be considered for trastuzumab therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
95
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(102 citation statements)
references
References 22 publications
5
95
2
Order By: Relevance
“…Due to the limited efficacy and severe complications of surgery and radiotherapy, a more systematic therapeutic approach should be analyzed in order to improve the prognosis of SDC. The present study demonstrated a high positivity rate for HER-2/neu and AR expression in SDC, indicating that SDC carcinogenesis may resemble that of breast ductal carcinoma or prostate cancer (4,7,11,13,15,18,21,22). As HER-2/neu blockers (trastuzumab) are effective in treating HER-2-overexpressing breast cancer, this agent may be useful for the treatment of SDC.…”
Section: A B C D Esupporting
confidence: 49%
See 1 more Smart Citation
“…Due to the limited efficacy and severe complications of surgery and radiotherapy, a more systematic therapeutic approach should be analyzed in order to improve the prognosis of SDC. The present study demonstrated a high positivity rate for HER-2/neu and AR expression in SDC, indicating that SDC carcinogenesis may resemble that of breast ductal carcinoma or prostate cancer (4,7,11,13,15,18,21,22). As HER-2/neu blockers (trastuzumab) are effective in treating HER-2-overexpressing breast cancer, this agent may be useful for the treatment of SDC.…”
Section: A B C D Esupporting
confidence: 49%
“…Similarly, androgen deprivation therapy may be applied to the treatment of SDC. These two therapeutic strategies have achieved positive results in a small number of cases of head and neck SDC (11,15,22). Clinicians may expect monoclonal antibody treatments to be a promising adjuvant therapy for SDC, however, this field requires additional research prior to the application of such therapies.…”
Section: A B C D Ementioning
confidence: 99%
“…Although salivary duct carcinoma is one of the most aggressive salivary gland malignancies, the patient reported here is free of metastasis and recurrence 36 months after the surgery. In addition, this type of cancer strongly expr-essed HER2/neu is more aggressive than those without HER2/neu expression [1,13]. The reasons of favorable prognosis of this patient are not known.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemcal observation in this case revealed similar findings reported previously. Cancer cells were strongly positive for AR [17] and HER2/neu [13], but negative for S-100 [1]. However, only a few cancer cells were weakly positive for apocrine marker GCDFP-15, in contrast to previous reports [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the c-erbB-2 is expressed by high grade carcinomas as salivary duct carcinoma, high grade carcinoma, and exclusively by the malignant component of carcinoma ex pleomorpic adenoma (Johnson et al, 2008;Nabili et al, 2007;Matsubayashi & Yoshihara, 2007). Although the latter may present myoepitelial derivation, carcinoma ex pleomorphic adenoma probably adquired a particular biological behavior in the longstanding process of malignant transformation.…”
Section: Discussionmentioning
confidence: 99%